The effect of varying pulp reagent chemistry on the flotation performance of a South African PGM ore. (September 2016) - Moimane, T.M.; Corin, K.C.; Wiese, J.G.
Graphical abstract: Highlights: Increased collector dosages may lead to froth destabilisation. Collector behaviour may be impacted by the ionic nature of the plant water. Increased ionic strength of plant water did not adversely affect the metallurgical performance. Abstract: The pulp chemistry plays a pivotal role during the extraction of commodities in the PGM industry as they employ the froth flotation separation process, which is based on the selective alteration of surface properties between the valuable minerals and undesired gangue. The chemical environment is intricate owing to the multiple and various surface reactions occurring at the mineral surface, and the increased ionic concentrations due to the practice of water recycling. Thus, a holistic understanding of the pulp chemistry is sought. By conducting bench scale flotation tests at varying concentrations of flotation reagents and typical ions present in plant water, it is possible to better understand the role of pulp chemistry on metallurgical plant performance. The effects of such variations, which modify the chemical environment of the pulp and impact plant performance, are discussed in this paper.